2017
DOI: 10.1039/c7ra01501a
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the neonicotinoid insecticide acetamiprid in surface water by the bacterium Variovorax boronicumulans CGMCC 4969 and its enzymatic mechanism

Abstract: The plant growth-promoting rhizobacterium Variovorax boronicumulans CGMCC 4969 was used to degrade the neonicotinoid insecticide, acetamiprid (AAP), in surface water, and the enzymatic mechanisms of AAP degradation in V. boronicumulans CGMCC 4969 were explored. V. boronicumulans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…The environmental fate of acetamiprid has attracted considerable attention, and microbial degradation is the key means for the dissipation of acetamiprid from the environment (15,16). In recent years, several microbial strains capable of degrading acetamiprid have been isolated, and the catabolic pathways of acetamiprid have been extensively studied (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Four catabolic pathways of acetamiprid are illustrated in Fig.…”
mentioning
confidence: 99%
“…The environmental fate of acetamiprid has attracted considerable attention, and microbial degradation is the key means for the dissipation of acetamiprid from the environment (15,16). In recent years, several microbial strains capable of degrading acetamiprid have been isolated, and the catabolic pathways of acetamiprid have been extensively studied (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Four catabolic pathways of acetamiprid are illustrated in Fig.…”
mentioning
confidence: 99%
“…The molar transformation rate (the total amounts of IAM and IAA divided by the consumed amount of IAN) at 72 h was 86.6%, which indicated that the synthesis of IAM and IAA was the main pathway of IAN metabolism in strain CGMCC 4969. CGMCC 4969 NHase is a cobalt-dependent metalloenzyme, and adding cobalt ions apparently enhanced its activity (15,16). As Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Characterization of V. boronicumulans CGMCC 4969 nitrile-converting enzymes. In V. boronicumulans CGMCC 4969, NHase activity for transforming IAN to IAM has been confirmed (16). The putative nitrilase-coding genes nitA and nitB and indoleacetamide hydrolase-coding genes iamA and iamB were overexpressed in E. coli Rosetta(DE3)/pLysS.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations